2013
DOI: 10.1111/jth.12061
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant F8 gene intron 1 inversion with concomitant duplication and deletion in a severe hemophilia A patient from Southern Italy

Abstract: Intron 1 and intron 22 inversions (inv1 and inv22) represent the most prevalent mutations in the F8 gene (F8) (1-5% and 40-45%, respectively) causative of severe haemophilia A (HA) [1]. These alterations result from intrachromosomal recombination between intronic regions (int1h-1 and int22h-1, respectively) and their homologous extragenic copies in the telomeric position (int1h-2 and int22h-2/3, respectively) [1]. Inv1 causes an altered F8 structure with the translocation and inversion of the 5¢ region includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 11 publications
(12 reference statements)
1
17
1
Order By: Relevance
“…To date, no study has reported this large duplication of the F8 exon 1 in the international HA mutation database [http://www.eahad-db.org/], in the scientific literature, or in the CNV database [http://projects.tcag.ca/variation/], nor has it been described in studies of over 300 patients from the general Belgian population. Nevertheless, three complex rearrangements involving severe HA patients have previously been reported describing duplications of F8 intron 1 that, contrary to our cases, were associated with a classical inversion of intron 1 . Recessive von Willebrand disease type 2 Normandy, transmitted as recessive disorder, could theoretically be ruled out, given the clearly inherited X‐linked recessive HA in the three families that has been present for at least four generations.…”
Section: Discussioncontrasting
confidence: 67%
“…To date, no study has reported this large duplication of the F8 exon 1 in the international HA mutation database [http://www.eahad-db.org/], in the scientific literature, or in the CNV database [http://projects.tcag.ca/variation/], nor has it been described in studies of over 300 patients from the general Belgian population. Nevertheless, three complex rearrangements involving severe HA patients have previously been reported describing duplications of F8 intron 1 that, contrary to our cases, were associated with a classical inversion of intron 1 . Recessive von Willebrand disease type 2 Normandy, transmitted as recessive disorder, could theoretically be ruled out, given the clearly inherited X‐linked recessive HA in the three families that has been present for at least four generations.…”
Section: Discussioncontrasting
confidence: 67%
“…Genomic inversion does not normally result in gain or loss of DNA, but unusual patterns have been described in Inv22 and Inv1 that lead to the hypothesis of more complex rearrangements involving deletions or duplications [14][15][16][17][18][19][20][21][22][23][24][25][26]. Furthermore, mechanisms causing these complex rearrangements are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Others are mediated by int22h/int1h copies without producing inversions . These have all been identified during F8 routine genetic analyses of Inv22 and Inv1 and classified as aberrant Inv patterns . They consist of both deletions and duplications, and could be more common than expected.…”
Section: Risk For Carriers Of F8 Inversionsmentioning
confidence: 99%
“…This additional event could be missed by routine genetic analyses as usual methods for Inv detection (southern blot or polymerase chain reaction [PCR] approaches) only detect DNA sequences around inth copies. This is unfortunate, as the combination of int22h ‐related inversion and large deletion in the F8 gene could be associated with X‐linked moyamoya angiopathy syndrome, and could additionally significantly increase the risk for developing high levels of inhibitors . It has been shown that genotypes with Inv22 maintain the possibility of F8 transcription.…”
Section: Risk For Carriers Of F8 Inversionsmentioning
confidence: 99%
See 1 more Smart Citation